2014
DOI: 10.1080/00102202.2014.967397
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Surface Advection in Transient Periodic Flow

Abstract: The advection of an interface by a known transient periodic excitation flow is investigated in the present study, the results of which are relevant to the propagation of nearly isothermal premixed flames in turbulent flow. The relation between the corrugated-surface area and the intensity of the excitation flow is obtained numerically and compared with exact analytically derived solutions. The results elucidate the relation between the surface area and the intensity of spatial and temporal flow-field variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In premixed turbulent combustion, burning velocity is enhanced linearly by low-intensity turbulence. For a better understanding of the relationship between flame surface advection and the intensity of the excitation flow, Aldredge [46] studied the advection of a flame front in a transient periodic flow (spatially and temporally) wherein different levels of turbulent intensity (low, moderate and large) of flow perturbations were considered analytically and numerically. The results were consistent with those obtained in the earlier investigations [44].…”
Section: The Effect Of Flow Oscillation On Turbulent Combustionmentioning
confidence: 99%
“…In premixed turbulent combustion, burning velocity is enhanced linearly by low-intensity turbulence. For a better understanding of the relationship between flame surface advection and the intensity of the excitation flow, Aldredge [46] studied the advection of a flame front in a transient periodic flow (spatially and temporally) wherein different levels of turbulent intensity (low, moderate and large) of flow perturbations were considered analytically and numerically. The results were consistent with those obtained in the earlier investigations [44].…”
Section: The Effect Of Flow Oscillation On Turbulent Combustionmentioning
confidence: 99%
“…It was concluded that at least part of the "bending effect," which is normally seen in premixed combustion occurring in high-intensity turbulence [5], results from local flame stretch modifying the local consumption speed. For a better understanding of the relationship between flame surface advection and the intensity of flow excitation, Aldredge [6] studied the advection of a flame front in a transient periodic flow (spatially and temporally) where different levels of turbulent intensity of flow perturbations were considered analytically and numerically. In recent research, Aldredge [7], has studied the flame surface and burning rate increase due to wrinkling by analyzing the effect of multiscale periodic transient flow on isothermal-flame propagation.…”
Section: Introductionmentioning
confidence: 99%